A Novel Hypomorphic CSF1R Gene Mutation in the Biallelic State Leading to Fatal Childhood Neurodegeneration - Tamhankar, Parag Mohan; Zhu, Bin; Tamhankar, Vasundhara Parag; Mithbawkar, Shilpa; Seabra, Luis; Livingston, John H.; Ikeuchi, Takeshi; Crow, Yanick J. (Neuropediatrics, 2020)
We report the clinical and molecular characterization of a novel biallelic mutation in the CSF1R gene leading to an autosomal recessive form of childhood onset leukoencephalopathy in a consanguineous family. The female child experienced acute encephalopathy at the age of 2 years, followed by spasticity and loss of all achieved milestones over 6 months. Her elder brother presented with encephalopathy at 4 years of age, with a subsequent loss of all achieved milestones over 8 months. Brain imaging in both children revealed multiple well-defined areas of calcification in the parietal and frontal regions and the occipital horns of both lateral ventricles. Clinical exome trio analysis showed homozygosity for a p.T833M mutation in CSF1R in the girl. Heterozygous family members, including both parents, were asymptomatic, with the eldest being 68 years of age. Total CSF1R protein expression levels were normal as compared with wild-type allele, but CSF1 ligand dependent autophosphorylation was consistent with a hypomorphic allele.
Keywords: CSF1R; adult onset leukoencephalopathy with axonal spheroids and pigmented glia; recessive; hypomorph; biallelic; India